Development of a Web-Based Health Information System Integrated with Artificial Intelligence Using Agile Methodology at Dasan Agung Primary Health Center - Muhamad Masjun Efendi; Ardiyallah Akbar; Lalu Mutawalli (Ninety Media Publisher, 2026)
The recording of health data at the Dasan Agung Community Health Center(Puskesmas) in Mataram City is still carried out manually, giving rise tovarious problems such as data entry errors, data loss, delays in data retrieval,and inaccuracies in health reports. This study aims to develop a Web-BasedHealth Data Recording Information System using the Agile method to enhancethe effectiveness of health data management at the community health center.The method employed encompasses the stages of requirements gathering, analysis,design, coding, testing, deployment, and feedback. Data collection wasconducted through observation, interviews, and documentation studies. Thesystem was built using the PHP programming language with the CodeIgniter3.1.13 framework and a MySQL database. The findings indicate that the developedsystem is able to facilitate a more effective, faster, and integrated healthdata recording process. Available features include patient data management,personnel data management, patient registration, drug data management,laboratory management, medical records, patient prescriptions, and digitalhealth reports. With the implementation of this system, health administrationprocesses become more optimal and support the digital transformation ofhealth services at the community health center. The outputs of this researchare a web-based information system and the publication of a scientific articlein a national journal.